2015
DOI: 10.1002/chem.201503219
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenated Graphenes by Birch Reduction: Influence of Electron and Proton Sources on Hydrogenation Efficiency, Magnetism, and Electrochemistry

Abstract: Interest in chemical functionalisation of graphenes today is largely driven by associated changes to its physical and material properties. Functionalisation with hydrogen was employed to obtain hydrogenated graphenes (also termed graphane if fully hydrogenated), which exhibited properties including fluorescence, magnetism and a tuneable band gap. Although the classical Birch reduction has been employed for hydrogenation of graphite oxide, variation exists between the choice of alkali metals and alcohols/water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 56 publications
(112 reference statements)
1
23
0
Order By: Relevance
“…Advancing on our previous reports of direct Birch reduction on graphite oxide (GO), we now show that the use of halogenated graphenes as starting material, instead of GO, considerably improves the hydrogen storage up to 7.44 wt%, which is a marked improvement in gravimetric hydrogen content. Since the graphene scaffold is a light‐weight material and its hydrogenated product is stable at both room temperature and on atmospheric exposure, additional equipment (such as tanks, pressure regulators, or insulation, which weigh down the system) are not required, as with conventional compressed hydrogen storage methods; thus strengthening its potential in meeting the U.S. DOE's ultimate system target.…”
Section: Introductionsupporting
confidence: 59%
“…Advancing on our previous reports of direct Birch reduction on graphite oxide (GO), we now show that the use of halogenated graphenes as starting material, instead of GO, considerably improves the hydrogen storage up to 7.44 wt%, which is a marked improvement in gravimetric hydrogen content. Since the graphene scaffold is a light‐weight material and its hydrogenated product is stable at both room temperature and on atmospheric exposure, additional equipment (such as tanks, pressure regulators, or insulation, which weigh down the system) are not required, as with conventional compressed hydrogen storage methods; thus strengthening its potential in meeting the U.S. DOE's ultimate system target.…”
Section: Introductionsupporting
confidence: 59%
“…It has been demonstrated that single‐layer graphene is hydrogenated uniformly, but graphene with more layers and sealed edges is not, which supports the idea that hydrogenation occurs from the edges of graphene by intercalation of alkali metal into the structure, where the defects are located . A comprehensive study of the alkali metal used for reduction in NH 3 and various proton sources yielded graphanes with various hydrogen content, and revealed that the best combination, Na in NH 3 with water as a proton source, yielded graphane with composition of C 1.4 H 1 O 0.3 . Besides graphene, carbon nanotubes can be opened by potassium in NH 3 to yield graphane nanostripes with well‐defined structure .…”
Section: Synthesis Of Graphene Derivativesmentioning
confidence: 99%
“…[71a] Ac omprehensive study of the alkali metal used for reduction in NH 3 and various proton sourcesy ieldedg raphanes with varioush ydrogen content, and revealed that the best combination, Na in NH 3 with water as ap roton source, yielded graphane with composition of C 1.4 H 1 O 0.3 . [78] Besides graphene,c arbon nanotubes can be openedb yp otassium in NH 3 to yield graphane nanostripesw ith well-defined structure. [79] Also, various other graphite-based nanostructures were used for the synthesis of graphane-based sheetsw ith controlled morphology.…”
Section: Sulfur Functionalities On Graphenementioning
confidence: 99%
“…The influence of electron and proton sources on the hydrogenation efficiency during Birch reduction has been thoroughly examined. It was concluded that water as a quenching agent and potassium as a source of electrons represent the optimal combination to achieve the highest degree of hydrogenation . The modified Birch reduction method (Benkeser reaction), utilizing alkyl amine as a solvent (allowing to perform the reaction at room temperature), has been used for graphene hydrogenation .…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that water as aq uenching agent and potassiuma sasource of electrons represent the optimal combination to achieve the highest degree of hydrogenation. [18] The modified Birch reduction method (Benkeser reaction), utilizing alkyl amine as as olvent (allowing to perform the reaction at room temperature), has been used for graphene hydrogenation. [19] The last category of graphane preparation combines various synthetic approaches.…”
Section: Introductionmentioning
confidence: 99%